History of Science and Its Interlocutors in the Humanities - Arabatzis, Theodore (Centaurus, 2024)
Since the early days of its professionalization, in the aftermath of the Second World War, the history of science has been seen as a bridge between the natural sciences and the humanities. However, only one aspect of this triadic nexus, the relations between the history of science and the natural sciences, has been extensively discussed. The other aspect, the relations between the history of science and the humanities, has been less commented upon. With this paper I hope to make a small step towards redressing this imbalance, by discussing the relationships between the history of science and two other humanistic disciplines that have been historically and institutionally associated with it: the philosophy of science and general history. I argue that both of these relationships are marked by the characteristics of an unrequited friendship: on the one hand, historians of science have ignored, for the most part, calls for collaboration from their philosopher colleagues; and, on the other hand, historians specializing in other branches of history have been rather indifferent, again for the most part, to the efforts of historians of science to understand science as a historical phenomenon. I attempt to offer a diagnosis of this regrettable situation and a suggestion for overcoming it.